Sphingosine 1‐Phosphate Prevents Human Embryonic Stem Cell Death Following Ischemic Injury. Issue 7 (24th May 2022) - Assis, Juliane L. de; Fernandes, Aline M.; Aniceto, Bárbara S.; Pompeu, Pedro; Banchio, Claudia; Girardini, Javier; Vieyra, Adalberto; Valverde, Rafael H. F.; Einicker‐Lamas, Marcelo
Abstract: Cell therapy based on humanembryonic stem cells (hESCs) is a potential treatment for several human diseases caused by ischemic processes. Efficiency and feasibility of these therapies rely on understanding stem cell biology and the interaction and survival of these cells within the injured tissue. hESCs are an important source of diffusible bioactive paracrine modulators and the targets for different signaling molecules that prime cellular tissue repair. Notably, sphingosine 1‐phosphate (S1P) is an emerging bioactive lipid that activates G protein‐coupled receptors, known as S1P receptors (S1PR1–5), promoting cell survival, differentiation, and migration. It is shown that S1P increases cell viability and prevents death in about 50% after the ischemic insult. S1P‐mediated protectiveeffect is attributed to the modulation of S1PR3 and S1PR4 expression, which have been associated with the reperfusion injury salvage kinase/survivoractivating factor enhancement (RISK/SAFE) pathway. Involvement of the SAFE pathway is further verified by applying Janus Kinase (JAK2) and signal transducer and activation of transcription 3 pathway inhibitors, which prevents the S1P protective effect. An increase in sphingosine kinase (SphK) activity is also observed after S1P pretreatment. These results provide evidence for an S1P‐dependent, SphK positive feedback that stimulates hESCs to deliver large amounts of S1P. Thus, S1P protects hESC under ischemic conditions through the different receptors. Practical Applications : It is considered that S1P can be used as an adjuvant to pretreat hESCs prior to the administration in cell therapy‐based protocols for different diseases. Abstract : Sphingosine 1‐phosphate (S1P) promotes the remodeling of S1P receptors upon injury and also activates an intracellular positive feedback increasing sphingosine kinase (SphK) activity in an S1P‐dependent manner. A) Basal homeostasis of the S1P/S1PR/SPK axis. Upon an ischemic injury, a fraction of the cells will die. B) S1P pretreated human embryonic stem cell present an altered localization of S1P receptors, priming reperfusion injury salvage kinase/survivor activating factor enhancement (RISK/SAFE), leading to an intracellular positive feedback that augments SphK activity in an S1P‐dependent manner promoting cell survive.